1999
DOI: 10.1021/es990380s
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Environmental Gradient:  Anthropogenic Influences on the Spatial and Temporal Distributions of Lead and Zinc in Sediments

Abstract: Urban settings are a focal point for environmental contamination due to emissions from industrial and municipal activities and the widespread use of motor vehicles. As part of the National Water-Quality Assessment Program of the U.S. Geological Survey, streambedsediment and dated reservoir-sediment samples were collected from the Chattahoochee River Basin and analyzed for total lead (Pb) and zinc (Zn) concentrations. The sampling transect extends from northern Georgia, through Atlanta, to the Gulf of Mexico an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(130 citation statements)
references
References 14 publications
7
120
0
3
Order By: Relevance
“…The urbanesuburbanerural gradient pattern is common in the context of rapid urbanization in China, and strongly affects land use zoning, population density, the proportion of surfaces that are impervious, traffic density, energy consumption, street cleaning methods, and spatial distribution of manufacturers (Callender and Rice, 2000;Zhao et al, 2011). Previous studies indicated that the urbanerural gradient had an important effect on RDS amounts, grain size composition, metal types and concentrations associated with it (Rogge et al, 1993;Kupiainen et al, 2005;Kim and Sansalone, 2008;Thorpe and Harrison, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The urbanesuburbanerural gradient pattern is common in the context of rapid urbanization in China, and strongly affects land use zoning, population density, the proportion of surfaces that are impervious, traffic density, energy consumption, street cleaning methods, and spatial distribution of manufacturers (Callender and Rice, 2000;Zhao et al, 2011). Previous studies indicated that the urbanerural gradient had an important effect on RDS amounts, grain size composition, metal types and concentrations associated with it (Rogge et al, 1993;Kupiainen et al, 2005;Kim and Sansalone, 2008;Thorpe and Harrison, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of population growth, urban areas have been increasing in the study area, and the urban expansion rate from 1996 to 2005 was much higher than that in the previous decades, indicating more intensive land conversions from forest, cropland and other land use types to urban areas. Much concern on negative impacts of urban expansion has been raised, special attention should be paid to quantifying urbanization-induced changes in water quality, hydrology and biodiversity in rivers and coastal areas [10,11,13].…”
Section: Implications For Land Use Policy Makersmentioning
confidence: 99%
“…High proportions of impervious surface lead to increasing nutrient and sediment loads to streams [11]. Urban developments were reported to increase heavy metals, bacteria loadings, temperatures and other nutrients in streams [12][13][14]. Forest plantation for commercial purposes could dramatically alter water cycling through enhancing evapotranspiration and deteriorate water quality through applications of chemical fertilizers and pesticides [15].…”
Section: Introductionmentioning
confidence: 99%
“…The urban-suburban-rural gradient pattern is has been strongly affected by rapid urbanization in China, and in turn affects land use zoning, population density, proportion of impervious surfaces, traffic density, energy consumption, street cleaning methods, and spatial distribution of manufacturers [6,22]. Therefore, the urban-rural gradient could affect the amounts and proportions of different chemical fractions of heavy metals in RDS and washoff particles by influencing the particle size of RDS, the metals associated with RDS and the RDS washoff process.…”
Section: Introductionmentioning
confidence: 99%